Analysis of Slaughtering Points Distribution during Eid al-Adha 1440H in Malang City, East Java, Indonesia - Adrenalin, Sruti Listra; Airlangga, Gegana Wimaldy; Hardian, Andreas Bandang (Veterinary Biomedical and Clinical Journal, 2020)
Eid al-Adha is an annual Muslim celebration throughout the world indicated by sacrificing animals such as cattles, goats or sheep. This study aimed to analyse the distribution of slaughtering points, types and the number of animals being slaughtered as well as antemortem and postmortem abnormalities of the carcasses during Eid al-Adha 1440 H in Malang City. Data were collected from the geocode service location and the secondary data were obtained through questionnaire. This study listed a total of 145 slaughtering points located in Blimbing, Kedung Kandang, Klojen, Lowokwaru, and Sukun District with 3102 animals being sacrificed. The slaughtering points were taken place in the office yards, mosque yards, home yards, school yards or other public fields. As many as 75.86% of slaughtering points provided special shelters for the animals before being slaughtered. The antemortem examination resulted that animals from 21.38% of the slaughtering points suffered from conjunctivitis, lesions on the skin, broken horns, and lameness. Proportions of apparent postmortem abnormalities were measured respectively: cattle 64.83%, goat 41.38%, and sheep 4.14%.Â  Hence, we recommend to further involve the veterinarians to monitor the animal condition during Eid al-Adha and to ensure the slaughtering processes were done properly.